NUAK1 (ARK5) is Associated with Poor Prognosis in Ovarian Cancer. - Neil T. Phippen; Nicholas W. Bateman; Guisong Wang; Kelly A. Conrads; Wei Ao; Tracy A. Litzi; Julie Oliver; George L. Maxwell; Chad A. Hamilton; Kathleen M Darcy; Thomas Conrads (Frontiers in Oncology, 2016)
Background and Objective: Nua kinase 1 (NUAK1) was identified in multigene signatures of survival and suboptimal debulking in high grade serous ovarian cancer (HGSOC). This study investigates the individual clinical and biologic contributions of NUAK1 in HGSOC patients and cell lines.Methods: Public transcript expression, clinical, and outcome data were used to interrogate the relationship between NUAK1 and clinicopathologic factors and patient outcomes including progression-free survival (PFS) and molecular subtypes using logistic and Cox modeling. Analysis of NUAK1 transcript expression was performed in primary tumors from 34 HGSOC patients with < or ≥ 2 years PFS. The impact of silencing NUAK1 by RNA interference on the migratory potential and chemosensitivity of SOC cells was assessed in vitro.Results: Elevated NUAK1 transcript expression was associated with worse PFS (hazard ratio=1.134), advanced stage (odds ratio, OR=1.7), any residual disease (OR=1.58), and mesenchymal disease subtype (OR=7.79 ± 5.89). Elevated NUAK1 transcript expression was observed in HGSOC patients with < vs. ≥ 2 years PFS (p<0.045). RNA interference (RNAi)-mediated silencing of NUAK1 expression attenuated migration of OV90 and E3 HGSOC cells in vitro, but did not modulate sensitivity to cisplatin or paclitaxel.Conclusions. Elevated NUAK1 was associated with poor survival as well as advanced stage, residual disease after cytoreductive surgery and mesenchymal molecular subtype. NUAK1 impacted migration, but not chemosensitivity in vitro. Additional studies are needed to further develop the concept of NUAK1 as a clinically deployable biomarker and therapeutic target in HGSOC.